Generalized Ito Formula and Some Stochastic Inclusions (Journal of Nonlinear Modeling and Analysis, 2024)
This work is on a general integration by parts formula generalizingthe Ito formula. An application is given to stochastic inclusions which have adifferent form than usual.
Keywords: Ito formula; stochastic evolution inclusions.